Malaysian Electronic Commerce Act 2006 and EU Directives: Consumer Protection Perspectives (Journal of Governance and Development (JGD), 2007)
European Union (EU) has given directives as a guiding framework for enactment of laws to facilitate the growth of e-commerce contract and transaction in that region. Malaysia has enacted Electronic Commerce Act 2006 to smoothen the progress of e-commerce in Malaysia. Though section 2(1)(g) of Consumer Protection Act 1999 has been deleted to include consumers’ transaction electronically, Electronic Commerce Act is still important in governing the online contract as a whole. This article will seek to highlight the similarities and differences between the Electronic Commerce Act 2006 and the EU Directives on certain issues of online contracting which relate to consumer protection.